2019
DOI: 10.1186/s12909-019-1563-5
|View full text |Cite
|
Sign up to set email alerts
|

Developing creative and research skills through an open and interprofessional inquiry-based learning course

Abstract: Background Biomedicine needs innovative professionals. Inquiry-based learning (IBL) aims to develop higher order thinking skills, such as creativity and research. Stimulatory techniques and interprofessional education, which requires students from different fields to collaborate, also enhances creativity. In this study, the effectiveness of an interprofessional IBL course that introduces a creativity workshop based on stimulatory techniques to develop creative and research skills is examined. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
33
0
8

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 36 publications
5
33
0
8
Order By: Relevance
“…The results of the intervention go in line with Rodríguez et al (2019) who found that inquiry-based learning -in our case, it is a research-oriented approach -develops the research and creative thinking skills. Additionally, it generally improves the students' academic results.…”
Section: Discussionsupporting
confidence: 84%
“…The results of the intervention go in line with Rodríguez et al (2019) who found that inquiry-based learning -in our case, it is a research-oriented approach -develops the research and creative thinking skills. Additionally, it generally improves the students' academic results.…”
Section: Discussionsupporting
confidence: 84%
“… Was the declaration of interest stated? Van Lierop et al (2019) [ 51 ] Yes Yes No Yes Yes Yes Yes Yes No No Unclear No Yes No Yes Rodríguez et al (2019) [ 52 ] Yes Yes Yes Yes Yes Yes Yes Yes Yes Yes Yes Yes Yes Yes Yes Van Gessel et al (2018) [ 1 ] Yes Yes Unclear Yes Yes Yes Yes Yes Yes Yes Unclear Yes Yes Yes Yes Imafuku et al (2018) [ 53 ] Yes Yes Yes Yes Yes Yes Yes Unclear Yes Yes Yes Yes Yes No Yes Milot et al (2015) [ 54 ] Yes No No Yes Yes Yes Yes Yes NA a NA NA NA No No Yes Sanborn H. (2016) [ 30 ] Yes Unclear No Yes Yes Yes …”
Section: Resultsmentioning
confidence: 99%
“…As shown in Table 2 , the evaluation of IPE programme outcomes based on the modified Kirkpatrick’s framework revealed changes in IPE participants’ knowledge or skills (Level 2b) in 50% ( n = 8) of the included studies [ 45 – 47 , 52 , 53 , 55 , 56 , 58 ]. Six studies (37.5%) reported changes in pre-licensure students’ attitude (Level 2a) toward IPE [ 1 , 45 – 47 , 51 , 58 ], whereases seven studies (43.75%) demonstrated a change in organisational practice (Level 4a) after the implementation of IPE [ 30 , 46 , 48 50 , 57 , 58 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The development of research skills for many pedagogical professions commences in undergraduate education yet there is limited evidence regarding effective research teaching and learning approaches. According to (G. Rodríguez, N. Pérez, G. Núñez [1]; J. Topalov, B. Radić-Bojanić [2]) the main goal of recearch activity is to consolidate and to deepen knowledge which are received by students within the process of training, to acquire the necessary research skills. For most of this century, and increasingly in modern times, teacher educators have been impelled to consider ways in which a greater level of reflectivity, especially through enhancing research skills development, might be integrated into the teacher education program (T. Lovat, M. Davies, R. Plotnikoff [3]).…”
Section: Introductionmentioning
confidence: 99%